MENGGUGURKAN KANDUNGAN HASIL PEMERKOSAAN MENURUT YUSUF AL-QARDHAWI - Muhammad Aminullah (Fakultas Syariah IAI Muhammadiyah Bima, 2017)
The main point of this essay is the study of Islamic Law about “Perspective of Yusuf Al-Qardhawi at abort the fetus which is effected by rape”. The problem formulations are; firstly what is the law of abort the fetus which effected by rape based on Yusuf Al-Qardhawi’s perspective?, second what the kind of approach to take and set the law by Yusuf Al-Qardhawi to that case? The writer uses the multidisciplinary approach, the instruments of data analyze are deductive, inductive and collaborative. While, to collect the data, writer used the literature approach. The result of this research show that, firstly the law of abort the fetus effected by rape is allowed or legalized based on Yusuf Al- Qardhawi’s perspective, it to be rukhsah to who pregnant due to the rape, except it, if not aborted so will disturb the pregnant safety. But, abort should be done before 40 days of fetus age. Second, Yusuf Al-Qardawi used the Qiyas method to decide the case, it mean that the woman is allowed to abort in an emergency. If it not, so will disturb the pregnant safety, as known that, the core of pregnant is fetus. Finally, the result of research describe how moderate of Yusuf Al-Qardawi to get the benefit of human.